Pemetaan Daya Dukung Lingkungan Penyedia Air Bersih Berbasis Jasa Ekosistem di Tarempa Kabupaten Anambas - Erik Febriarta; Lulu Mari Fitria; Karina Bunga Hati; Ahmad Ghazali; Deni Agus Setyono; Rakyan Paksi Nagara (Jurnal Wilayah dan Lingkungan, 2022)
Carrying capacity of the environment is a condition of the physical ability of the environment to be utilized and manageable to meet the needs of life and development of an area. Water resources are a basic need for human activities and living things around them. The environmental carrying capacity of the supply factor in the form of clean water is part of the strategic steps for environmental management and protection in the Anambas Islands. The study aims to determine the level of environmental carrying capacity of clean water supply factors. The study was conducted using the ecosystem service method. The parameters used for the calculation of carrying capacity are the ecoregion which provides information on the physical condition of the landscape with the same characteristics and characteristics, the land cover which provides corrections to land-based economy activities and hydrogeological conditions, which provide information on the availability of groundwater and the potential for water productivity. The three environmental data scores and weight values are graded using the analytical hierarchy process (AHP) and then are calculated linearly for all these variables, resulting in an environmental services index value. The value of environmental services is grouped into five classes, so it is known that the environmental carrying capacity of clean water providers on Siantan Island is 32.9% very high carrying capacity, 1.36% high carrying capacity, 6.2% medium carrying capacity, low carrying capacity 21 %, and the carrying capacity is very low 38.5%. In general, the environmental conditions of clean water providers on Siantan Island are very low.